Atomically Defined Co3O4(111) Thin Films Prepared in Ultrahigh Vacuum: Stability under Electrochemical Conditions - Faisal, Firas; Bertram, Manon; Stumm, Corinna; Cherevko, Serhiy; Geiger, Simon; Kasian, Olga; Lykhach, Yaroslava; Lytken, Ole; Mayrhofer, Karl J. J.; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry C, 2018)
We have explored the stability, the structure, and the chemical transformations of atomically defined Co3O4(111) thin films under electrochemical conditions. The well-ordered Co3O4(111) films were prepared on an Ir(100) single crystal under ultrahigh vacuum (UHV) conditions and subsequently transferred and characterized in the electrochemical environment by means of cyclic voltammetry (CV), scanning flow cell inductively coupled plasma mass spectrometry (SCF-ICP-MS), and electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). We have found that the Co3O4(111) films are stable in phosphate buffer at pH 10 at potentials between 0.33 to 1.33 V-RHE. In the corresponding potential range, the corrosion rates established by means of SCF-ICP-MS were well below 0.1 monolayer per hour. Additionally, low-energy electron diffraction (LEED) and X-ray photoelectron spectroscopy (XPS) studies have shown that the long-range order, the thickness, and the composition of the films were preserved under electrochemical conditions. Disintegration of the film and formation of holes after repeated potential cycling within the stability window were ruled out by EC-IRRAS using CO as a probe molecule. In general, the stability of the Co3O4(111) films depends critically on both the pH and electrode potential. Increasing the pH from 10 to 12 compromised the structural stability of the Co3O4(111) films due to faster redox processes at the surface. In particular, we observed accelerated oxidation of cobalt followed by the formation of oxyhydroxide during the anodic scan and accelerated reduction to cobalt hydroxides during the cathodic scan. Decreasing the pH from pH 10 to pH 8, on the other hand, led to faster dissolution, in particular at potentials below 0.2 V-RHE, where the dissolution rate increased rapidly due to formation of soluble Co(II) species. Our studies demonstrate that thin well-ordered oxide films prepared in UHV can be transferred into the electrochemical environment while preserving their atomic surface structure if the conditions are chosen carefully. This opens a surface science approach to atomically defined oxide-electrolyte interfaces.